PENERAPAN MUHĀDATSAH AL-YAUMI DALAM PENINGKATAN KETERAMPILAN KALĀM PADA PONDOK PESANTREN DI SULAWESI SELATAN - Bahrun, Muhammad Farhan; Makmur, Reinizqy Mughniza; Azis, Abdul Jalil; Daroini, Slamet (STIQ Amuntai, 2024)
The emergence of challenges in learning Arabic has driven academics to use complex and efficient methods that have a direct impact on their implementation. Therefore, one method that is considered capable of providing tangible results is